Variations in volatile organic compounds in Zhenyuan Daocai samples at different storage durations evaluated using E-nose, E-tongue, gas chromatography, and spectrometry. (1st January 2023) - Liu, Xueting; Wang, Xueli; Cheng, Yanwei; Wu, Yuangen; Yan, Yan; Li, Zhen
Abstract: In this study, the changes in volatile organic compounds (VOCs) in Zhenyuan Daocai at different storage durations were determined using electronic tongue (E-tongue), electronic nose (E-nose), and other methods. Gas chromatography-ion mobility spectrometry (GC-IMS) identified 81 VOCs in Zhenyuan Daocai, which originated either from the raw materials or developed during processing and storage. Isothiocyanates were the characteristic VOCs in the raw materials of Zhenyuan Daocai, imparting a mustard flavor, heptanal, nonanal, 1-hydroxy-2-propanone, and 2-pentylfuran were the compounds obtained after processing, imparting orange, sweet, and nutty flavors. The characteristic VOCs observed in Daocai after one year of storage were (E, E) −2, 4-hexadienal, ethyl acetate, and isoamyl acetate, which contributed to the floral and fruity odors. The characteristic VOCs in Daocai after four years of storage were furfural, 2-methyl-3-furanthiol, and methyl butyrate, which contributed to the almond, roasted meat, fried coffee, and apple flavors. Graphical abstract: Image 1 Highlights: E-nose and E-tongue effectively detected changes in Zhenyuan Daocai aroma and taste. Differences in VOC of Zhenyuan Daocai were detected by HS-GC-IMS topographic plots. HS-SPME-GC-MS technology identified 179 volatile compounds present in the samples. All technologies could distinguish the Zhenyuan Daocai samples stored for different time periods. Changes in the VOC profiles of Zhenyuan Daocai increased with storage duration.